Campylobacter-like organisms and Candida in peptic ulcers and similar lesions of the upper gastrointestinal tract: a study of 247 cases. Issue 10 (October 1988) - Kalogeropoulos, N K; Whitehead, R
Abstract : Campylobacter-like organisms were detected by light microscopy in association with 57 of 102 (56%) of gastric ulcers, all the gastric erosions associated with gastritis, three of five (60%) of gastric erosions without gastritis, five of 13 (39%) of mild superficial gastritis and two of 36 (6%) of normal gastric mucosa. They were also seen in four of 20 (20%) of duodenal ulcers, but not in duodenal erosions with duodenitis or normal duodenal biopsy specimens. They were seen in association with 12 of 64 (19%) of cases of Barrett's oesophagus. Moniliasis was seen in nine of 78 (12%) of the gastric ulcers in which campylobacter-like organisms were found, and the incidence of moniliasis was three of 15 (20%) in association with duodenal ulcers when ulcer debris was present in biopsy material, and in association with six of 25 (24%) of cases of Barrett's oesophagus. These findings do not support the hypothesis that campylobacter-like organisms cause inflammatory and ulcerative lesions of the upper gastrointestinal tract.